TINGKAT DAYA TAHAN AEROBIK (VO2 MAX) PEMAIN BOLA VOLI PUTRA UKM OLAHRAGA STKIP MODERN NGAWI - Aldila Maulana; Kartika Septianingrum; Kuncoro Darumoyo (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The purpose of this study was to determine the level of aerobic endurance of members of the Volleyball UKM Sports STKIP Modern Ngawi, so that coaches and members can find out the level of aerobic endurance possessed by members. This study is a descriptive study with a survey method and data collection using test and measurement techniques. The population used was all members of the Volleyball UKM Sports STKIP Modern Ngawi, totaling 24 people. The sample taken from the total sampling results was 24 people. Data on the aerobic endurance of members of the Volleyball UKM Sports STKIP Modern Ngawi was taken by measuring using a multistage fitness test. The data analysis technique in this study used quantitative descriptive analysis with a percentage. Based on the study, it can be seen that the level of aerobic endurance in the very good category is 4.1% with a frequency of 1 player. The good category is 41.6% with a frequency of 10 players. The moderate category is 33.3% with a frequency of 3 players. The less category with a percentage of 8.3% with a frequency of 2 players. Based on these data, the level of aerobic endurance of male volleyball players of UKM Olahraga STKIP Modern Ngawi is in the good category.